Vocal Ornamentation Style of Sri Hartati in the Keroncong Song Bandar Jakarta by Iskandar - Suryati, Suryati; Legino, Rafeah; Artanto, Mei; Anugerah, Hafidz Akbar (Resital: Jurnal Seni Pertunjukan, 2025)
Vocal ornamentation is very necessary for a singer. Vocal ornamentation can be applied to several genres of songs, one of which is keroncong songs. In performing keroncong songs, both Keroncong Asli, Langgam and Stambul have their own characteristic vocal ornamentation. Each singer also has their own characteristics in performing Keroncong songs. Therefore, this study focused on Sri Hartati's vocal ornamentation style in performing the Keroncong song "Bandar Jakarta" Ciptaan Iskandar. Therefore, this research can be used as a reference and study material in Keroncong learning at the Music Education Study Program of the Indonesian Institute of the Arts Yogyakarta. This study used qualitative method with contents analysis. Analysis was conducted for Sri Hartati's vocal ornamentation style in singing the song "Kr. Bandar Jakarta" which includes cengkok, gregel, luk, embat and nggandul. This study aims to provide an overview of vocal ornamentation for students who take keroncong courses, especially as vocals or keroncong singers. The results showed that Sri Hartati's vocal ornamentation style was dominated by luk, even though there were cloves and gregel.  Sri Hartati's vocal ornamentation style is simple but has its own uniqueness, so many achievements at the national level.